2013
DOI: 10.2147/ndt.s36453
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin for the treatment of generalized anxiety disorder: an update

Abstract: A previous review summarized what was then known about the potential role of pregabalin in the treatment of patients with generalized anxiety disorder (GAD): this review provides an update on its pharmacological properties and presumed mechanism of action, the liability for abuse, and efficacy and tolerability in patients with GAD. Pregabalin has a similar molecular structure to the inhibitory neurotransmitter gamma amino butyric acid (GABA) but its mechanism of action does not appear to be mediated through ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 118 publications
1
50
0
5
Order By: Relevance
“…We also found that GCSR was sensitive to pregabalin (a calcium channel inhibitor), which is positive in our rodent RSA test [90], effective in generalised anxiety disorder [115], and has not been reported to be clinically either primarily by the preSMA [99] With somewhat slower go responses stopping is controlled primarily by rIFG [97,98] but BIS output is too slow to affect stopping in the SST [102].With even slower go responses (as in go/no go tasks) activation of the BIS would generate response inhibition via rIFG/preSMA. avPFC = anteroventral prefrontal cortex; preSMA = presupplementary motor area; rIFG = right inferior frontal gyrus.…”
Section: Importantly We Also Have Unpublished Datasupporting
confidence: 59%
“…We also found that GCSR was sensitive to pregabalin (a calcium channel inhibitor), which is positive in our rodent RSA test [90], effective in generalised anxiety disorder [115], and has not been reported to be clinically either primarily by the preSMA [99] With somewhat slower go responses stopping is controlled primarily by rIFG [97,98] but BIS output is too slow to affect stopping in the SST [102].With even slower go responses (as in go/no go tasks) activation of the BIS would generate response inhibition via rIFG/preSMA. avPFC = anteroventral prefrontal cortex; preSMA = presupplementary motor area; rIFG = right inferior frontal gyrus.…”
Section: Importantly We Also Have Unpublished Datasupporting
confidence: 59%
“…There is no known untoward interaction with lithium. Spontaneous reports of adverse sexual side effects are uncommon but the incidence of treatment-emergent sexual dysfunction with pregabalin is uncertain [IV] (Baldwin et al, 2013). Discontinuation symptoms after abrupt withdrawal of pregabalin have been reported, as has the abuse of pregabalin generally in individuals with a history of other substance abuse: but the relative potential for developing tolerance and abuse, when compared to with medications, is not established [IV] (Baldwin et al, 2013).…”
Section: Pregabalinmentioning
confidence: 99%
“…By changing the conformation of the calcium channel, pregabalin is proposed to: reduce the release of excitatory neurotransmitters such as glutamate, reduce the synthesis of excitatory synapses, and block the progression of new calcium channels to the cell surface. 22 Pregabalin has robust evidence in the treatment of GAD both in the acute phase and in relapse prevention. 1,22 It has evidence of efficacy in young patients and the elderly, and may enhance the effects of an SSRI or SNRI.…”
Section: Pregabalinmentioning
confidence: 99%
“…22 Pregabalin has robust evidence in the treatment of GAD both in the acute phase and in relapse prevention. 1,22 It has evidence of efficacy in young patients and the elderly, and may enhance the effects of an SSRI or SNRI. 22 NICE recommends pregabalin as a treatment option if the SSRIs or SNRIs are poorly tolerated in GAD.…”
Section: Pregabalinmentioning
confidence: 99%
See 1 more Smart Citation